2016
DOI: 10.1186/s12954-016-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Peer-engagement and its role in reducing the risky behavior among crack and methamphetamine smokers of the Downtown Eastside community of Vancouver, Canada

Abstract: BackgroundThe role of peers (former or current drug users) in reducing risky behavior within methamphetamine and crack smokers has not been well described or researched. The current study not only explores the role of peers in reducing risk factors for morbidity within the illicit drug smoking population in the Downtown Eastside (DTES) community of Vancouver but it also investigates the changes in the nature of drug use after the closure of an unsanctioned smoking facility.MethodsThe data pertain to qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…Step gGmbH [ VANDU's unsanctioned inhalation facility Bathroom with ventilation system [15] Inhalation room with fan accessible to one person at a time [41] Storefront location with a lobby, front desk area, injection room, and small adapted washroom with ventilation system accessible to one person at a time [16] Denmark Aarhus DCR 5 spaces for injection and 2 spaces for inhalation [78] Injection room, smoking room, health clinic [36] Maendenes Hjem Various rooms for different purposes including an injection and smoking room [88] Skyen Spaces for injection and inhalation (air conditioned) [53] 8 spaces for injection and 6 spaces for inhalation [78] 7 spaces for inhalation [44] Booths for injection and a separate room for inhalation [36] Germany Abrigado 4 spaces for injection and 4 spaces for inhalation [38] 10 rooms for different purposes; 4 spaces for injection and 4 spaces for inhalation [33] Birkenstube 6 spaces for injection/intranasal and 4 spaces for inhalation [43] DCR Bonn Ground floor: care area with lounge and kitchen First floor: counselling centre for drug use Second floor: medical clinic (outpatient) Third floor: crisis intervention (inpatient; short term; maximum 6 clients) Backyard: 5 spaces for injection and 3 spaces for inhalation [44] Drob Inn 10 spaces for injection and 5 spaces for inhalation/intranasal [43] 7 spaces for injection and 3 spaces for inhalation [38] 15 rooms for different purposes; 7 spaces for injection and 3 spaces for inhalation [33] 7 spaces for injection and 3 spaces for inhalation [42] DroBill 6 spaces for injection and 1 space for inhalation [38] 8 rooms for different purposes; 8 spaces for injection and 1 space for inhalation [33] Drogenberatung Bielefeld e.V. 8 spaces for injection/intranasal and 8 spaces for inhalation [43] Drogenhilfe Aachen~ 14 rooms for different purposes; 2 spaces for injection and 2 spaces for inhalation [33] Drogenhilfezentrum Saarbrücken gGmbH 13 spaces for injection/intranasal and 3 spaces for inhalation [43] Drogennotdienst Frankfurt 10 spaces for injection/intranasal and 5 spaces for inhalation [43] Düsseldorfer Drogenhilfe e.V.…”
Section: Characteristics Of Existing Scsmentioning
confidence: 99%
See 2 more Smart Citations
“…Step gGmbH [ VANDU's unsanctioned inhalation facility Bathroom with ventilation system [15] Inhalation room with fan accessible to one person at a time [41] Storefront location with a lobby, front desk area, injection room, and small adapted washroom with ventilation system accessible to one person at a time [16] Denmark Aarhus DCR 5 spaces for injection and 2 spaces for inhalation [78] Injection room, smoking room, health clinic [36] Maendenes Hjem Various rooms for different purposes including an injection and smoking room [88] Skyen Spaces for injection and inhalation (air conditioned) [53] 8 spaces for injection and 6 spaces for inhalation [78] 7 spaces for inhalation [44] Booths for injection and a separate room for inhalation [36] Germany Abrigado 4 spaces for injection and 4 spaces for inhalation [38] 10 rooms for different purposes; 4 spaces for injection and 4 spaces for inhalation [33] Birkenstube 6 spaces for injection/intranasal and 4 spaces for inhalation [43] DCR Bonn Ground floor: care area with lounge and kitchen First floor: counselling centre for drug use Second floor: medical clinic (outpatient) Third floor: crisis intervention (inpatient; short term; maximum 6 clients) Backyard: 5 spaces for injection and 3 spaces for inhalation [44] Drob Inn 10 spaces for injection and 5 spaces for inhalation/intranasal [43] 7 spaces for injection and 3 spaces for inhalation [38] 15 rooms for different purposes; 7 spaces for injection and 3 spaces for inhalation [33] 7 spaces for injection and 3 spaces for inhalation [42] DroBill 6 spaces for injection and 1 space for inhalation [38] 8 rooms for different purposes; 8 spaces for injection and 1 space for inhalation [33] Drogenberatung Bielefeld e.V. 8 spaces for injection/intranasal and 8 spaces for inhalation [43] Drogenhilfe Aachen~ 14 rooms for different purposes; 2 spaces for injection and 2 spaces for inhalation [33] Drogenhilfezentrum Saarbrücken gGmbH 13 spaces for injection/intranasal and 3 spaces for inhalation [43] Drogennotdienst Frankfurt 10 spaces for injection/intranasal and 5 spaces for inhalation [43] Düsseldorfer Drogenhilfe e.V.…”
Section: Characteristics Of Existing Scsmentioning
confidence: 99%
“…4 spaces for injection/intranasal and 6 spaces for inhalation (8 parallel consumptions maximum) [43] 6 spaces for injection and 2 spaces for inhalation [38] 10 rooms for different purposes; 5 spaces for injection and 3 spaces for inhalation [33] Stay Alive 8 spaces for injection, inhalation, and intranasal [43] 6 spaces for injection and 2 spaces for inhalation [38] 13 rooms for different purposes; 6 spaces for injection and 2 spaces for inhalation [33] 6 spaces for injection and 2 spaces for inhalation [42] Suchthilfe direkt Essen 8 spaces for injection/intranasal and 5 spaces for inhalation [43] Suchthlife Aachen 5 spaces for injection; 2 of which are for inhalation [43] The Essen DCR 8 spaces for injection and 4 spaces for inhalation [89] Verein für Gefährdetenhilfe 5 spaces for injection/intranasal and 3 spaces for inhalation [43] Luxembourg Abrigado Injection room and inhalation room (which opened in 2012) [90] Injection room with 8 tables and inhalation room with 6 tables [46] 7 spaces for injection and 3-4 spaces for inhalation (pilot project; February 2012) [1] Supervised injection and inhalation room [91] Netherlands In total, articles provided details on staffing for 41 (85%) of the identified SCS that permit alternate routes of consumption. Of these 41 SCS, 35 (85%) discussed employing healthcare professionals (e.g., nurses, physicians), 16 (39%) discussed employing social workers, 27 (66%) discussed employing counsellors, 2 (5%) discussed employing peer workers ("…members of the community who have experience in safe illicit drug practices" [15]), and 35 (85%) discussed employing other staff (e.g., outreach workers, security guards, volunteers). Both of the SCS that employ peer workers were in Canada.…”
Section: Name Layout Citationmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most successful treatment forms that has proven to be effective in reducing negative mental health stigma and improving access to support services is peer-based programs (Greden et al 2010). Not only are peer-based programs extremely cost-effective, they also promote treatment for all individuals (Nowotny et al 2017;Greden et al 2010;Jozaghi et al 2016). We urge governments to invest in low-barrier mental health drop-in centres, and peerbased mental health training programs for first responders, specifically for PWUDs in the affected regions.…”
Section: Next Stepsmentioning
confidence: 99%
“…In addition to operating the only legally sanctioned supervised injection facility in North America, Vancouver has benefited from numerous community harm reduction consumption facilities that previous research has shown to have clear benefits . Moreover, the harm reduction program in Vancouver has focused on utilizing peer drug user networks which has proved to be extremely effective in reducing mortality rates in Vancouver . Vancouver is also the only city in North America that has been implementing heroin‐assisted treatment .…”
Section: Introductionmentioning
confidence: 99%